Key participants in combating terrorism. - McDonald, M.D (IEEE Engineering in medicine and biology magazine)
Four recommendations are made to optimize the role of American citizens and their communities in homeland security and other societal functions being shaped in association with homeland security. These four recommendations are centered on democratic principles that would engage the public more directly in homeland security and a public health response to reduce the probability of deaths, negative health effects, and other adverse outcomes associated with asymmetric warfare. They cover: public health surveillance and maintaining fundamental rights; risk communications, citizen decision-making, and martial law; community-based health alert systems; and citizens acting together to reduce risks and improve their communities